ALAT PENGHITUNG BERAT BADAN MANUSIA DENGAN STANDART BODY MASS INDEX (BMI) MENGGUNAKAN SENSOR LOAD CELL BERBASIS ARDUINO MEGA 2560 R3 - Dewantara, Dewantara; Sasmoko, Priyo (Gema Teknologi, 2015)
Dewantara, Priyo Sasmoko, in this paper explain that a measuring instrument is a tool used by humans to help determine parameters such as height and weight. Most height and weight gauges used today still use simple and still conventional equipment. In addition, if manually, there are still frequent measurement errors that come from the measuring instrument itself or from the human. This happens because of inaccuracies in reading measuring instruments that lack precision or perhaps from the human factor itself. The purpose of this study was to create a digital height and weight automation system accompanied by displaying its ideal weight based on height. This system is built using Arduino as a system controller. The ultrasonic sensor is used as a measure of height. Load cell is used as a measure of weight. And a 20x4 LCD to display the output. From testing and analyzing the results of measurements of height according to the actual height, the results of measurements of weight have an error percentage of 0.53% - 2.77%. The system determines the ideal or not body weight based on BMI. Keywords: 20x4 LCD, Load Cell Sensor, Arduino.ReferencesFogaswara, Eka. 2013. Prinsip Dasar Kelistrikan dan konversi energy untuk SMK/MAK. Bandung: CV ARMICO.Massimo dkk, Arduino/Genuino Mega 2560. 28 Juli 2015.  https://www.arduino.cc/en/Ma in/ArduinoBoardMega2560. Diakses pada 28 Juli 2015.Anonim. Sensor. 5 September 2015. http://id.wikipedia.org/wiki/sensor. Diakses  pada 5 September 2015Anonim. HX711 Weight Scale ADC Modul. 6 September 2015. http://www.vcc2gnd.com/Diakses pada 6 September 2015Arifai, Samsul. Dkk, 2014, Rangkain Catu Daya. http://s3.amazonaws.com/academia.e du.documents/ Diakses  pada 24 Agustus 2015Malvino, Prinsip-prinsip Elektronika, Buku satu, Salemba Teknika, hal 66Anonim. Catu daya. 6 September 2015. http://profil.widodoonline.com /Elektronika/komponen/praktik um/teori-dasar-catu-daya.html